2021
DOI: 10.3390/ph14060566
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptides: Identification of two Beta-Defensins in a Teleost Fish, the European Sea Bass (Dicentrarchus labrax)

Abstract: Beta-defensins consist in a group of cysteine-rich antimicrobial peptides (AMPs), widely found throughout vertebrate species, including teleost fish, with antimicrobial and immunomodulatory activities. However, although the European sea bass (Dicentrarchus labrax) is one of the most commercially important farmed fish species in the Mediterranean area, the characterization of its beta-defensins and its potential applications are still missing. In this study, we characterized two members of the beta-defensin fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…The milk‐isolated biologically active peptides play a vital role in human health, but their mechanism of action is still not very clear. Several studies have found that various animal and food sources of BAPs, such as milk and milk proteins, egg, fish, frogs, wheat, meat, and rapeseed, have immunomodulatory (Korhonen, 2009), antihypertensive (García‐Tejedor et al, 2015; Iram et al, 2022; Singh et al, 2020; Solanki & Hati, 2018; Zhang et al, 2020), antioxidant (Panchal et al, 2020, 2021; Toropova et al, 2021), antimicrobial (Abdel‐Hamid et al, 2020; Abdou et al, 2007; Algboory & Muhialdin, 2021; Barroso et al, 2021; Benkerroum et al, 2010; Matin & Otani, 2002; Miao et al, 2016; Rahman et al, 2020; Sansi et al, 2022; Tang et al, 2015; Théolier et al, 2013) and antidiabetic properties (Lafarga et al, 2014). BAPs are mostly derived from casein and whey proteins (Tagliazucchi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The milk‐isolated biologically active peptides play a vital role in human health, but their mechanism of action is still not very clear. Several studies have found that various animal and food sources of BAPs, such as milk and milk proteins, egg, fish, frogs, wheat, meat, and rapeseed, have immunomodulatory (Korhonen, 2009), antihypertensive (García‐Tejedor et al, 2015; Iram et al, 2022; Singh et al, 2020; Solanki & Hati, 2018; Zhang et al, 2020), antioxidant (Panchal et al, 2020, 2021; Toropova et al, 2021), antimicrobial (Abdel‐Hamid et al, 2020; Abdou et al, 2007; Algboory & Muhialdin, 2021; Barroso et al, 2021; Benkerroum et al, 2010; Matin & Otani, 2002; Miao et al, 2016; Rahman et al, 2020; Sansi et al, 2022; Tang et al, 2015; Théolier et al, 2013) and antidiabetic properties (Lafarga et al, 2014). BAPs are mostly derived from casein and whey proteins (Tagliazucchi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the expression of immune gene-related in fish is a vital tool to clarify information on the mode of action of the application of herbal supplements in aquaculture [ 5 ]. Upregulation in the expression of HSP70 [ 39 ], Chicken type-lysozymes (c-type lysozymes) [ 40 ] and Beta-defensins [ 41 ] improves the antioxidant ability of cells, innate immune systems and modulation of immune activities following administration of immunostimulants. Our findings suggest that the application of GBNL has the potential to upregulate the expression of HSP70, c-type lysozymes and Beta-defensin in Nile tilapia, with significant effects with the dose application of 5gkg −1 in which the expression of immune-regulated genes seem to have reached their peak and declined afterwards.…”
Section: Discussionmentioning
confidence: 99%
“…Natural antimicrobial peptides (AMPs) have been found not only in marine fish [ 71 , 72 ] but also in marine invertebrates [ 73 , 74 ] as major components of their innate host defense systems. The Antimicrobial Peptide Database (APD, , accessed on 20 December 2022), online since 2003 and last updated in June 2022 [ 75 ], defines four unified classes of AMPs on the basis of the polypeptide chain’s connection patterns: (I) linear polypeptide chains (e.g., cathelicidins) [ 76 ]; (II) sidechain-linked peptides, such as disulfide-containing defensins and lantibiotics (i.e., lanthionine-containing antibiotics, e.g., microbisporicin, produced by the soil actinomycete Microbispora corallina [ 77 ] and mathermycin from the marine actinomycete Marinactinospora thermotolerans [ 78 ]); (III) polypeptide chains with side chain to backbone connection (e.g., bacterial lassos and fusaricidins); and (IV) circular peptides with a seamless backbone, i.e., N- and C-termini linked by a peptide bond (e.g., plant cyclotides and animal θ-defensins) [ 79 ].…”
Section: Linking Chemical Diversity Of Secondary Metabolites To Biosy...mentioning
confidence: 99%